Call Center Outsourcing Contracts Under Information Asymmetry - Hasija, Sameer; Pinker, Edieal J.; Shumsky, Robert A. (Management Science, 2008)
In this paper, we examine contracts to coordinate the capacity decision of a vendor who has been hired by a client to provide call center support. We consider a variety of contracts, all based on our observations of contracts used by one large vendor. We examine the role of different contract features such as pay-per-time, pay-per-call, service-level agreements, and constraints on service rates and abandonment. We show how different combinations of these contract features enable client firms to better manage vendors when there is information asymmetry about worker productivity. In particular, we focus on how different contracts can coordinate by yielding the system-optimal capacity decision by the vendor and consider how profits are allocated between the client and the vendor.